Garanzie personali e servizi dei confidi alle banche “dopo” Basilea 2 - Lanzavecchia, Alberto (Piccola Impresa / Small Business, 2010)
Since they have been established, Italian mutual guarantees funds (Confidi) played a key role in financial intermediation to SME. In the current scenario, which is the value perceived by banks of Confidi’s credit risk mitigation services? Do banks demand new services that Confidi could supply? To answer these research questions, we addressed to senior loan officers of a sample of Italian banking groups a questionnaire. Emerged that Banks are willing to pay for risk mitigation instruments and buy value-added services such as information collection and ex post monitoring.